Psychosocial Adaptation of International Students: Advanced Screening - Melnichuk, Marina (International Journal of Psychosocial Rehabilitation, 2018)
Considering the significance of academic adaptation of international students, it is important to examine problems of psychosocial adjustment taking into account presence/absence of psychotraumatic experience. This empirical study investigated how general mental health state, satisfaction with life, perceived social support, self-esteem and traumatic experience influenced academic adaptation in university. The present research used author's Migrants Psychosocial Maladjustment Scale (MPMS) created as a psychological diagnostic tool that helps estimating the degree of psychosocial maladjustment of temporary migrants. The MPMS results allowed analyzing the sample of international students from the point of view of psychosocial maladjustment. The obtained data proves significant influence of acquired traumatic experience and its consequences in form of different severity of mental disorder on adaptation process. In particular, 83% of the total number of respondents turned out to have different traumatic experience, 13.2% of which were diagnosed with PTSD symptoms of high and average severity. The most common respondents' reactions to traumatic events were sleeping problems, depressive and     social stress disorders. Results of the                                           study allow recommending used set of psychodiagnostic tools for psychosocial maladjustment screening of international students.